Very simple markov-perfect industry dynamics: Empirics - Jaap H. Abbring; Jeffrey R. Campbell; Jan Tilly; Nan Yang (Federal Reserve Bank of Chicago, 2018)
This paper develops an econometric model of firm entry, competition, and exit in oligopolistic markets. The model has an essentially unique symmetric Markov-perfect equilibrium, which can be computed very quickly. We show that its primitives are identified from market-level data on the number of active firms and demand shifters, and we implement a nested fixed point procedure for its estimation. Estimates from County Business Patterns data on U.S. local cinema markets point to tough local competition. Sunk costs make the industry's transition following a permanent demand shock last 10 to 15 years.
Keywords: L13; C25; C73; 330; demand uncertainty; dynamic oligopoly; firm entry and exit; nested fixed point estimator; sunk costs; toughness of competition; counterfactual policy analysis